(Mis)communication between educational policy and practice: teachers’ perceptions of educational policy communication during COVID-19 - Flora Woltran; Katharina-Theresa Lindner; Susanne Schwab (Cogent Education)
The advent of COVID-19 has brought with it an unprecedented shift to remote learning. For educators worldwide, this transition has been fraught with challenges, often characterized by a sense of instability. In such trying times, effective leadership is of paramount importance. By providing guidance and support, education policymakers can help educators navigate the complexities of distance learning and ensure that students receive a high-quality education. Against this backdrop, in the present investigation, two sub-studies were combined to investigate how Austrian teachers perceive the professional communication of education policy representatives. Study 1 includes data from 907 teachers from Austria collected via an online survey, and Study 2 includes data from 5 teachers who participated in an additional interview study. Data were collected when new COVID-19-related measures came into force in November 2021, which included the short-term abolition of compulsory attendance in face-to-face classes. The results show that, overall, teachers were explicitly dissatisfied with the quality and quantity of information provided by education policy stakeholders. Furthermore, the findings suggest that education policymakers have failed to provide clear guidance in a timely manner in uncertain times. The results of the study are discussed in terms of input and output legitimacy.